2012
DOI: 10.1021/mz300215u
|View full text |Cite
|
Sign up to set email alerts
|

Cross Nucleation in Polyethylene with Precisely Spaced Ethyl Branches

Abstract: In cross nucleation, an early nucleating crystalline polymorph (A) nucleates another crystalline polymorph (B) of higher or lower thermodynamic stability without undergoing a polymorphic transformation. Although this phenomenon was recently observed in the crystallization process of several small molecules, there has been insufficient evidence for cross nucleation in a crystalline polymer. In this paper, we report cross nucleation behavior during an isothermal crystallization of a crystalline polymer with prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…Cross-nucleation has been reported in experiments for small organic molecules such as the polymorph-rich organic compound ROY, 9, 16-20 D-mannitol, 11, 21 glycine, 21 and D-sorbitol, 22,23 and -recently -for polymers such as polyethylene 17 and poly(1-butene). 24 Cross-nucleation has also been studied through molecular simulations for LennardJones [25][26][27] and Yukawa 28 crystals, and in methane clathrate a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Cross-nucleation has been reported in experiments for small organic molecules such as the polymorph-rich organic compound ROY, 9, 16-20 D-mannitol, 11, 21 glycine, 21 and D-sorbitol, 22,23 and -recently -for polymers such as polyethylene 17 and poly(1-butene). 24 Cross-nucleation has also been studied through molecular simulations for LennardJones [25][26][27] and Yukawa 28 crystals, and in methane clathrate a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 87%
“…5,21,33 A complete picture of how a polymorph can grow on other crystal, or why is one form preferred over the other, is not yet available. 8,17,24,33 Previous studies indicate that faster growth rate of the new crystal is a necessary but not sufficient condition for cross-nucleation. 9,10,16,20 Defects 16 on the seed crystals as well as their crystallographic orientation 11 have been proposed to influence the possibility of cross-nucleation.…”
Section: Introductionmentioning
confidence: 99%
“…Two ethyl branches are included in the crystalline structure, which destabilizes the hexagonal phase, causing the nucleation and growth of a spherulite . The resulting crystallite seems to be triclinic …”
Section: Alkyl‐branched Admet–polyethylenementioning
confidence: 99%
“…More recently, sporadic work on cross‐nucleation in semicrystalline polymers also appeared . Cavallo and Alfonso have shown that many more overlooked examples exist in the polymer crystallization literature .…”
Section: Introductionmentioning
confidence: 99%
“…13 More recently, sporadic work on cross-nucleation in semicrystalline polymers also appeared. 19,20 Cavallo and Alfonso have shown that many more overlooked examples exist in the polymer crystallization literature. [21][22][23] Moreover, systematic extension of a quantitative approach to cross-nucleation to different macromolecules (isotactic poly(1-butene), polypivalolactone and isotactic polypropylene) [23][24][25][26][27][28] allowed us to understand that the nucleation of one polymorph on another can be regarded as a special case of heterogeneous nucleation, unless the parent phase grows at rates comparable to those of the daughter polymorph.…”
Section: Introductionmentioning
confidence: 99%